Drying Apricots on the Basis of New Technologies - Qobilov Kh.X; Sharipova N.R; Salimova S.A. (Genius Journals, 2022)
More than 60% of the population of the country is engaged in the cultivation of agricultural products. One of the most pressing issues is the export of finished and semifinished products obtained through the processing of agricultural products, as well as the supply of high quality, affordable products for the consumption of our people, the development and application of new techniques and technologies for long-term storage. It is known that Uzbekistan is a leader in Central Asia in the production of agricultural products. An average of 5 million tons of fruits and vegetables are grown in the country annually, of which 107,000 tons are canned fruits and vegetables. From these fruits and vegetables are produced a variety of food products for consumption
Keywords: Drying; drying technology; sublimation drying; solar dryer